Problematika Problematika Tugas Mengajar Dengan Bidang Keahlian Guru - Heti Baniati; Muhammad Isnaini; Muhammad Fauzi (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to explore and describe the problems of teaching at SMP Negeri 7 Prabumulih. The research method used is a descriptive qualitative method with a case study research type. The main data or key informants in this study were the main subjects of the study, namely the principal and teachers (PAI, Natural Sciences, Social Studies, and English) of 10 SMP Negeri 7 Prabumulih concerned. The determination of respondents was based on teachers who were given teaching assignments not in accordance with their field of expertise and educational background. (determination of respondents and those studied). Secondary data or supporting data in this study include school principals, teachers, and documentation data. From the results of the study it was found that the problems of teaching teachers at SMPN 7 Prabumulih, teachers who were appointed to teach and were not in accordance with their areas of expertise encountered various problems in the process such as difficulty understanding the material, and students who also had difficulty absorbing explanations from the teacher, even though the school provided a strategy as an alternative to facilitate the teacher's task but still, as a necessity, a teacher is indeed required to harmonize between his field of expertise and his teaching duties.